Learning from The Collective Space in Making Culture and Making Space: A Case Study from Yogyakarta City, Indonesia - Larasati, Zita Wahyu; Pratiyudha, Pinurba Parama; Prabaningrum, Galih; Cahyati, Devy Dhian; Krisdyatmiko, Krisdyatmiko (Journal of Urban Culture Research, 2022)
The contestation of urban space is a dialectical process in defining space by stakeholders in urban areas. We will explain the efforts of city citizens to form a collective space by promoting a making culture. With the spirit of Do It Yourself and Do It With Others, the collective space produces shared knowledge and democratizes data to increase the capacity of urban citizens. This study is grounded on empirical research in Yogyakarta through in-depth interviews, focus group discussions, and participant observation. We discuss the formation of collective space in urban informality to encourage urban communities. This study finds that the collective space has collaborated with some local communities to promote the making culture and encourage individual creativity by contributing ideas and exploring new knowledge.